Designing Hydrogen‐Bonded Organic Frameworks (HOFs) with Permanent Porosity - Hisaki, Ichiro; Xin, Chen; Takahashi, Kiyonori; Nakamura, Takayoshi (Angewandte Chemie International Edition, 2019)
Designing organic components that can be used to construct porous materials enables the preparation of tailored functionalized materials. Research into porous materials has seen a resurgence in the past decade as a result of finding of self‐standing porous molecular crystals (PMCs). Particularly, a number of crystalline systems with permanent porosity that are formed by self‐assembly through hydrogen bonding (H‐bonding) have been developed. Such systems are called hydrogen‐bonded organic frameworks (HOFs). Herein we systematically describe H‐bonding patterns (supramolecular synthons) and molecular structures (tectons) that have been used to achieve thermal and chemical durability, a large surface area, and functions, such as selective gas sorption and separation, which can provide design principles for constructing HOFs with permanent porosity. HOF the shelf: Hydrogen‐bonded organic frameworks (HOFs) are described systematically based on hydrogen‐bonding patterns (supramolecular synthons) and molecular structures (tectons). HOFs can show thermal and chemical durability, a large surface area, and permanent porosity.